1982
DOI: 10.1159/000241509
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 3,5,3′-Triiodothyronine on Phosphoenolpyruvate Carboxykinase, Fatty Acid Synthetase and Malic Enzyme Activity of Liver and Brown Fat of Fetal and Neonatal Rats

Abstract: Pregnant rats were injected with triiodothyronine (T3) on the 19th and 20th days of pregnancy. This elevated fetal T3 plasma values and caused a large rise in fetal liver phosphoenolpyruvate carboxykinase (PEPcK) activity. At the same time PEPcK activity in fetal brown fat was inhibited. Essentially the same effect of T3 was also noted when injected into postnatal rats. T3 injections also elevated fatty acid synthetase activity in brown fat of weanling rats but, in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Additionally, studies performed in suckling rats injected with T 3 , during 2 d, reported no changes in the activity of the liver FAS (35). We observed in the liver of the pups a decrease in FAS activity at day 7 and of ACC activity at day 14 of lactation.…”
Section: Table 2 Effects Of Hyperthyroidism On Liver Triglyceride Andsupporting
confidence: 45%
“…Additionally, studies performed in suckling rats injected with T 3 , during 2 d, reported no changes in the activity of the liver FAS (35). We observed in the liver of the pups a decrease in FAS activity at day 7 and of ACC activity at day 14 of lactation.…”
Section: Table 2 Effects Of Hyperthyroidism On Liver Triglyceride Andsupporting
confidence: 45%
“…This suggests that T 3 rather than T 4 is the primary thyroid hormone involved in the developmental control of tissue gluconeogenic enzyme activity in utero . Indeed, previous studies have shown that raising the plasma T 3 concentration in fetal rats by maternal T 3 treatment close to term causes a significant increase in hepatic PEPCK activity (Hahn & Hassanali, 1982). Furthermore, direct intraperitoneal administration of thyroid hormones to the rat fetus accelerates the normal maturational increase in hepatic G6P activity (Greengard, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic gluconeogenesis does not become active until shortly after birth (Schaub et al, 1972) and increases substantially and rapidly to levels above those in the adult liver (Beaudry et al, 1977). The high insulin‐to‐glucagon ratio in utero is quickly and substantially reversed in the early neonate (Fernández‐Milán et al, 2013; Girard, 1990; Hahn & Hassanali, 1982; Ktorza et al, 1985; Lyonnet et al, 1988). A reduced counterregulatory influence of insulin on hepatic glucose handling, potentially affecting either glucagon‐activated pathway, is an important hormonal component of the adaptive response in the neonate (Girard, 1990; Hahn & Hassanali, 1982; Mlekusch et al, 1981; Nurjhan et al, 1985).…”
Section: Role Of the Ac/camp Pathway In Meeting Elevated Glucose Dema...mentioning
confidence: 99%
“…The high insulin‐to‐glucagon ratio in utero is quickly and substantially reversed in the early neonate (Fernández‐Milán et al, 2013; Girard, 1990; Hahn & Hassanali, 1982; Ktorza et al, 1985; Lyonnet et al, 1988). A reduced counterregulatory influence of insulin on hepatic glucose handling, potentially affecting either glucagon‐activated pathway, is an important hormonal component of the adaptive response in the neonate (Girard, 1990; Hahn & Hassanali, 1982; Mlekusch et al, 1981; Nurjhan et al, 1985). A rise in plasma corticosteroid levels contributes to the enhancement of gluconeogenic gene expression (Ogias et al, 2010).…”
Section: Role Of the Ac/camp Pathway In Meeting Elevated Glucose Dema...mentioning
confidence: 99%